Common Stock Returns and Rating Changes: A Methodological Comparison - Griffin, Paul A.; Sanvicente, Antonio Z. (Journal of Finance, 1982)
This paper examines the adjustments in a firm's common stock price during the eleven months before and during the month of announcement of a bond rating change. Based on several different measures of abnormal security return, the findings are consistent with the proposition that bond downgradings convey information to common stockholders. For bond upgradings, the price adjustments were statistically insignificant in the month of announcement, although in the eleven preceding months, upgraded firms exhibited positive abnormal returns. While the results do not fully support earlier research, we stress that the main contribution of this article lies in the scrutiny it gives to issues of methodology in assessing the possible price effects of bond reclassifications.